Impact of biochar addition on soil properties and water-fertilizer productivity of tomato in semi-arid region of Inner Mongolia, China - Li, Changjian; Xiong, Yunwu; Qu, Zhongyi; Xu, Xu; Huang, Quanzhong; Huang, Guanhua (Geoderma, 2018)
Biochar is proposed as a soil amendment to improve soil physical-chemical properties and crop productivity. However, the effect of biochar on crop yield is not consistent and the mechanisms affecting plant growth are still not well-understood. In this paper, field experiments were carried out to investigate the impact of biochar addition on soil properties, water and fertilizer productivity of tomato in semi-arid area of Inner Mongolia, China. The tested biochar was made from maize straw by slow pyrolysis. Four biochar treatments were conducted including addition of 10, 20, 40 and 60 t ha−1 and no biochar as a control. Addition of biochar reduced the bulk density and increased the porosity of soil. Electrical conductivity of soil increased with increasing biochar application rate. Soil pH was not affected by addition of biochar in one growing season. Yield, crop water productivity and partial factor productivity for fertilizer were nonlinearly (quadratic) proportional to application rate of biochar. Highest water and fertilizer productivity obtained from the 40 t ha−1 biochar treatment. Comprehensive analysis of biochar impact on yield, water and nutrient productivity, and cost-benefit for the grower indicate that addition of approximate 30 t ha−1 is an appropriate rate for tomato production in the study area. This suggestion is based on the relatively short term effect and local market conditions. A prolonged experiment is desirable to understand the long term response of soil and crop to biochar addition. •Addition of biochar improves soil and water conditions thus increasing tomato growth in sandy loam soil.•Water productivity and partial factor productivity for fertilizer are nonlinearly proportional to application biochar rate.•An appropriate biochar strategy for application is proposed for tomato production in sandy loam soil of semi-arid region.